JOYFUL ASIAN YOUTH! LIVING THE GOSPEL IN MULTCULTURAL ASIA - Alphonsus Boedi Prasetijo (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Reflecting on the theme: “Joyful Asian Youth! Living the Gospel in Multicultural Asia”, we can start by enjoying the theme song AYD 2017 Indonesia entitled JOYFUL! LIVING THE GOSPEL and based on the publications in HIDUP Catholic Magazine.First, we reflected Saint John Paul II spirituality as the founder of World Youth Day (WYD) and Asian Youth Day (AYD). Second, we faced some youth activities in Indonesia, especially in some dioceses and parishes in the Archdiocese of Semarang. Some reflections and opinions on multiculturalism and pluralism in Indonesia enriched youth activities before Asian Youth Day (AYD). Third, Catholic youth studied to punakawan (actors in wayang) as part of activities in visitation to the parishes. This is one model of the Javanese youth creativities.